Exploring Ambiguity as a Literary Tool in Robert Frost’s Selected Poems: Insights from William Empson’s Theory of Ambiguity - Shafi, Sidra; Ayub, Samina; Ayub, Saadia (Pakistan Journal of Humanities and Social Sciences, 2024)
Robert Frost's poems are well known for their abundant ambiguity, which acts as a powerful literary tool influencing various meanings. This qualitative study explores the complex and dual reading phenomenon in the context of Frost’s poetry. It highlights as how ambiguity plays its crucial role in comprehending poetic compositions of Frost. This research delves deeply into poems such as "The Road Not Taken" and "Stopping by Woods on a Snowy Evening" in order to identify recurring themes and symbols that lend themselves to a variety of readings. The study examines the theory of ambiguity by William Empson (1930) from his book "Seven Types of Ambiguity," which discovers how ambiguity in Frost's language can create multiple layers of meanings and enriches the reader's perception in his poems. Empson's theory discusses that ambiguity isn't an imperfection rather a meditative and prodigious tool used by authors to produce rich and complex literary works. This research outlines literary exploration through close reading that reflects on how Frost's deliberate use of ambiguity encourages the readers to deeply engage with his poetry, manifesting personal insights and diverse comprehension. The findings help to explain ambiguity in literature and its impact on poetic meaning by highlighting Frost's aptitude in creating poems with deeper complexity and multi-layered meanings.